'Coastal Management Guide - Managing Coastal Erosion': A STEM education resource for secondary school teachers. (15th July 2022) - Turner, Ian L.; Harley, Mitchell D.; Hanslow, David J.; Kinsela, Michael A.; Splinter, Kristen D.
Abstract: " Hello, I'm a school student and we're doing a project about the coast, and I was wondering if you could talk to me about what you do or send me some information?". Many coastal scientists and engineers regularly experience similar emails and phone calls from secondary school students (typically ages 12–16) and it is often very rewarding to speak with and assist these bright, young, people. Motivated by the increasing number and frequency of these requests, presented here is an overview of the approach taken and lessons learnt by a group of university and government coastal researchers during the creation of a secondary school education resource. Underpinned by fundamental concepts of coastal science and coastal management, the resulting Coastal Management Guide – Managing Coastal Erosion is primarily targeted at STEM teachers, that spans and is explicitly linked to a broad range of national curriculum areas, including the physical sciences, physical and human geography, environmental sciences and mathematics. Developed around an enquiry-based mode of learning and employing the well-established Five Es 'engage, explore, explain, elaborate & evaluate' instructional model, the content of the Guide was designed to include all the background technical information and additional resources that are necessary for teachers to lead their students through the range of classroom activities provided. Freely available as both an online eBook and 70-page downloadable pdf, at the time of writing more than 90, 000 website views originating from 77 countries have been recorded, with the eBook used over 3000 times and more than 10, 000 pdf copies of the Guide downloaded. Importantly, during the development of the Guide several key lessons were learnt, that can assist other individuals or teams of researchers who may be motivated to extend the reach of their own research into the school classroom: (1) Seeking the assistance of curriculum experts and specialist STEM content creators is invaluable. (2) Don't underestimate your potential reach into a broad range of school curriculum areas that may extend well beyond the physical sciences. (3) Decide if your audience is individual students or alternatively their teachers, remembering that one teacher can deliver to many students. (4) Consider teachers' practical needs and preferences – for example, downloadable pdfs that can be printed and copied are highly regarded. (5) Seek user feedback to find out what does and doesn't work, and to potentially generate new ideas for the next version …. In outlining and summarising the approach that was used to develop the secondary school educational resource presented here, it is hoped that other coastal researchers may be stimulated and encouraged to also give it a go. To do so is both professionally and personally very rewarding. Highlights: 'Coastal management' is an expanding topic of study within secondary school curricula. Classroom resources developed with the guidance of curriculum experts will increase impact. Addressing the practical needs of teachers can maximise the number of students reached.